Strategi Pengukuran dan Penilaian dalam Menentukan Efektivitas Evaluasi Pembelajaran Mata Kuliah Pengembangan Fisik Motorik - Salihibudayah Surahman (Jurnal Euforia, 2026)
The Physical and Motor Development Course aims to build students' competencies in designingand evaluating gross and fine motor activities for early childhood. The effectiveness of learningin this course needs to be measured systematically so that graduates are able to apply it in thefield. This article describes measurement and assessment strategies to determine theeffectiveness of learning evaluation in the Physical and Motor Development Course. Thefindings of the study indicate that effectiveness can be determined through: 1) establishingmeasurable indicators of motor development, 2) using observation instruments, performancerubrics, and portfolios, 3) analyzing competency achievement and N-Gain of practice, and 4)student reflection and feedback. It is concluded that practice-based and observation-basedmeasurement and assessment strategies are highly effective for assessing the improvement ofcompetencies of prospective early childhood education teachers.